2015
DOI: 10.1001/jamaoncol.2015.0389
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Hospital and Surgeon Factors on the Prevalence of Axillary Lymph Node Evaluation in Ductal Carcinoma In Situ

Abstract: Despite guidelines recommending against axillary lymph node evaluation in women with DCIS undergoing BCS and uncertainty regarding its use with mastectomy, SLNB or ALND is performed frequently. Given the additional morbidity and cost of these procedures, alternative surgical approaches or prospective evaluation of the clinical benefit of axillary evaluation in women with DCIS is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 50 publications
0
30
0
Order By: Relevance
“…Morbidity is not neglectable and cost and resources have to be considered as well. Coromilas et al found an increasing use of SNB in the US in women treated with a mastectomy and they concluded that an additional prospective evaluation is needed to determine if there is a clinical benefit of SNB in women with DCIS [24].…”
Section: Discussionmentioning
confidence: 99%
“…Morbidity is not neglectable and cost and resources have to be considered as well. Coromilas et al found an increasing use of SNB in the US in women treated with a mastectomy and they concluded that an additional prospective evaluation is needed to determine if there is a clinical benefit of SNB in women with DCIS [24].…”
Section: Discussionmentioning
confidence: 99%
“…13,14 The primary indication of SLNB at the time of mastectomy for in-situ disease is to provide axillary staging in the event that invasive carcinoma is detected on final pathology. Although there are limited data showing the feasibility of SLNB following mastectomy, the identification rates are significantly lower 15 and ALND remains the standard of care for axillary staging in patients with a preoperative diagnosis of DCIS found to have concomitant invasive disease after mastectomy.…”
Section: Discussionmentioning
confidence: 99%
“…However, a substantial proportion of breast surgeons still perform SLNB in these cases, with an increasing trend over time . This discrepancy between guidelines and current clinical practice may reflect some uncertainty and a need for further research in this field, and some important clinical issues have been emerged . Indeed, if upstaging to invasive ductal carcinoma is found on final pathology, the patient would need a second surgical procedure to perform SLNB.…”
Section: Introductionmentioning
confidence: 99%